Successful response in advanced leptomeningeal disease from pleomorphic xanthoastrocytoma with BRAF/MEK inhibitors: a case report - Jacome, Maria A.; Macaulay, Robert J.; Peguero, Edwin; Cyriac, Sheethal; Sahebjam, Solmaz; Etame, Arnold B.; Yu, Hsiang-Hsuan Michael; Piña, Yolanda (Frontiers in Oncology, 2025)
Leptomeningeal disease (LMD) is a rare metastatic complication with a grim prognosis for most patients and limited treatment strategies. Therapy is adjusted to the primary tumor from which it arises. Targeted therapies and personalized medicine have become cornerstones in cancer treatment but its utility in LMD has been limited. In here we report a case of a female patient who developed LMD from a Pleomorphic Xanthoastrocytoma (PXA), BRAFV600-mutated, who has shown successful response to treatment with BRAF/MEKi (Encorafinib/Binimetinib) for over 3 years since initial LMD diagnosis. The effectiveness of therapy in this patient was initially observed as stable disease, with radiographic progression when BRAF/MEKi were withheld, and immediate tumor control achieved when reinstated. Despite being just one case, this hopefully could serve as proof-of-concept for use of targeted therapy for BRAF V600E-mutated tumors with LMD progression, sparing patients from alternative tumor control options such as radiation therapy.